1996
DOI: 10.1002/(sici)1096-9926(199603)53:3<168::aid-tera4>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic potential of almokalant, dofetilide, andd-sotalol: Drugs with potassium channel blocking activity

Abstract: Drugs with class III antiarrhythmic activity are potential human teratogens because of their ability to cause bradycardia in the embryo during the organogenic period. Three drugs with class III antiarrhythmic activity, almokalant, dofetilide and d‐sotalol, were compared in vitro using rat embryo culture. Each of these drugs caused a concentration‐dependent bradycardia in 11‐ or 13‐day rat embryos. For each drug the effective concentration was considerably greater than the human therapeutic plasma concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 15 publications
7
66
1
Order By: Relevance
“…Developmental toxicity occurred at doses causing no adverse effects in the mothers, with the exception of the two deaths that will be discussed later in this section. The observed sotalol-induced embryonic death in this study is in accordance with what has been shown for other Ikr blockers in studies in rats (Ban et al 1994;Spence et al 1994;Marks & Terry 1996;Webster et al 1996) and in mice (Skö ld & Danielsson, 2000). Single-dose administration during Day 9, 10, 11, 12, 13, or 14 of the selective Ikr blockers dofetilide and almokalant in rats (Spence et al 1994;Webster et al 1996) resulted in embryonic death.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Developmental toxicity occurred at doses causing no adverse effects in the mothers, with the exception of the two deaths that will be discussed later in this section. The observed sotalol-induced embryonic death in this study is in accordance with what has been shown for other Ikr blockers in studies in rats (Ban et al 1994;Spence et al 1994;Marks & Terry 1996;Webster et al 1996) and in mice (Skö ld & Danielsson, 2000). Single-dose administration during Day 9, 10, 11, 12, 13, or 14 of the selective Ikr blockers dofetilide and almokalant in rats (Spence et al 1994;Webster et al 1996) resulted in embryonic death.…”
Section: Discussionsupporting
confidence: 92%
“…In rodent embryos cultured in vitro during the susceptible period, a dose-dependent occurrence of embryonic bradycardia, arrhythmia and cardiac arrest has been noticed for almokalant and dofetilide (Spence et al 1994;Webster et al 1996) and L-691,121 (Ban et al 1994). The results in these in vivo and in vitro studies show a very good correlation between maternal concentrations, which were related with embryonic death, and concentrations that caused severe dysrhythmia.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations